Manajemen Komunikasi Badan Narkotika Nasional Kabupaten Bantul dalam Merehabilitasi Remaja Pengguna Narkoba - Putri, Mutiara Dahlia Elisa; Prathisara, Gibbran (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
This study focuses on the communication management implemented by the National Narcotics Agency (BNNK) of Bantul Regency in its rehabilitation efforts for adolescent drug users. Drug abuse in Indonesia, particularly in Bantul Regency, shows alarming figures, with victims coming from various groups, ranging from teenagers to the elderly. However, adolescents are the main target group in this rehabilitation program, considering that during adolescence there is a tendency for high curiosity that makes them vulnerable to drug abuse. This study also aims to understand how the communication management approach implemented by BNNK Bantul in assisting the rehabilitation process of adolescent drug users who have a desire to recover from their addiction and how communication management that includes planning, organization, implementation, and evaluation can support the rehabilitation process with a humanistic, educational approach, and involving family and community. This study uses a qualitative method with a descriptive approach. Data were obtained through primary and secondary data collection, including in-depth interviews with 5 informants selected through participatory observation, and documentation. All collected data were analyzed thematically and verified using triangulation techniques to ensure the accuracy and validity of the information. The results of the study show that structured and synergistically integrated communication can create an environment conducive to adolescent recovery, with appropriate message management, appropriate media, and regular evaluation as a basis for program improvement in the future.